Tafsir Tari Zapin Arab dan Melayu dalam Masyarakat Melayu - Robby Hidajat; Suyono Suyono; Joko Sayono; Muhammad 'Afaf Hasyimy; Desy Ratna Syahputri; Syed Ahmad Iskandar; Iziq Eafifi Bin Ismail; Norliza Bt Mohd Isa (Mahesa Research Center, 2021)
This article aims to describe and interpret the Zapin Arab and Zapin Malay dances. Zapin dance comes from Arabic and developed within the scope of the Malay community. At first the Zapin dance culture was brought by merchants from Gujarat to various regions in the archipelago in the XV century. Zapin dance has a heroic background, because the movement was originally a sense of uplifting the spirit of the companions of the prophet for war. The development of Zapin Arabic and Malay dances are both expressed in the form of performing arts. The problem in this research is focused on the structure of the Malay zapin dance. In order to approach this problem, the structuralism theory reference from Levi Strauss' model is used. Structural theory is applied to describe Malay society. The data were collected through statements and experiences of sources, observation, and document review, then analyzed descriptively qualitatively. Data analysis uses textual and contestual interpretations, namely interpreting denotative and connotative structures. This study concludes that, (1) the Arabic Zapin dance has Arabic cultural content, and (2) the Malay Zapin dance is an Islamic expression of Malay culture.